1973
DOI: 10.2307/1540153
|View full text |Cite
|
Sign up to set email alerts
|

The Switchover From Virgin to Mated Behavior in Female Cecropia Moths: The Role of the Bursa Copulatrix

Abstract: 1. Mating greatly increases the oviposition rate of female Cecropia silkmoths. 2. Implantation of the spermatheca from a mated female (either with or without sperm) into a virgin female did not alter the typical virgin oviposition pattern. 3. After implantation of the bursa copulatrix (minus the spermatophore) from a mated female, the virgin female oviposited eggs in the typical mated pattern. 4. Similar implantations of bursae from virgin females or from females which had mated with castrate males did not alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Other Lepidoptera including Z. dininia (Benz, 1969), A.assectella (Thibout, 1979), Trichoplusia ni (Karpenko & North, 1973), H.cecropia (Riddiford & Ashenhurst, 1973) and Pectinophora gossypiella (Lachance et al, 1978) also require the presence of normal sperm to initiate the mated ovipositional response. Apparently, eupyrene sperm mediate this switch, and in A.assectella their presence in the receptaculum seminalis of the spermatheca is necessary for both increased oocyte production and increased oviposition (Thibout, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Other Lepidoptera including Z. dininia (Benz, 1969), A.assectella (Thibout, 1979), Trichoplusia ni (Karpenko & North, 1973), H.cecropia (Riddiford & Ashenhurst, 1973) and Pectinophora gossypiella (Lachance et al, 1978) also require the presence of normal sperm to initiate the mated ovipositional response. Apparently, eupyrene sperm mediate this switch, and in A.assectella their presence in the receptaculum seminalis of the spermatheca is necessary for both increased oocyte production and increased oviposition (Thibout, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…the presence of sperm in the spermatheca, Taylor 1967; mating plugs, references in Ehrlich and Ehrlich 1978; male-contributed hormones or "anti-aphrodisiacs, " Gilbert 1976;Obara 1982; the presence of sperm or testicular fluids in the bursa copulatrix. Riddiford and Ashenhurst 1973;Sasaki and Riddiford 1984), these factors do not explain the quantity of material transferred by male Lepidoptera. Several studies have indicated that large ejaculates delay female remating (Labine 1964;Sugawara 1979;Rutowski 1980;Rutowski et al 1981;Rutowski 1984;Oberhauser 1989) and two of these (Labine 1964;Sugawara 1979) showed that, in at least some species, this effect is mechanical; the amount of material in a female's bursa copulatrix affects her receptivity to courting males.…”
Section: Introductionmentioning
confidence: 91%
“…The processing of seminal peptides in the female genital tract for the transfer into the circulatory system has also been demonstrated in insect species such as locust (Lay et al, 2004) and D. melanogaster Ram et al, 2005). In many moths, the presence of mating factors in the HL of mated females suggests their humoral route to induce post-mating changes (Riddiford and Ashenhurst, 1973;Obara, 1982;Raina, 1989). In mated females of H. armigera, we were unable to detect a change in DrmSP-IR levels in the reproductive tissues (Bu-St) and in the HL, despite its significant depletion from the MAG.…”
Section: Drmsp-ir In Female Tissuesmentioning
confidence: 99%